Variação genética do arapaçu-liso Dendrocincla turdina (Aves, Dendrocolaptidae) em uma população da Mata Atlântica. Uma contribuição para conservação dessas aves - Fazza, Ana Cristina (2010)
The Atlantic forest is reduced to less than 8% of its original extent, but still has one of the greatest diversity and endemism rates observed in the Neotropical forests. Therefore, this biome can be internationally considered an hotspot for conservation priority. Several taxa are threatened by the intense habitat fragmentation, particularly, some understory species of birds have a reduced ability of permanence in degraded places. Studies on the species Dendrocincla turdina demonstrate that it possesses sensitivity to local intense edge effects and it could even disappear at depleted environments. This lowers tolerance may be due to its high ecological specialization. We can verify the impacts of environmental degradation on the species through analysis of genetic diversity, which is made using molecular markers. A quite useful molecular marker for population studies are the microsatellites, however, some species have none described, preventing such analysis to be performed. Our aim was to identify and to characterize microsatellite loci for D. turdina and to analyze the genetic variability of a population of this species from an Atlantic Forest area in the Sao Paulo State, in order to contribute to the conservation of this species. It were identified and characterized nineteen microsatellite loci, of which 11 showed polymorphism for the studied population. So far there was not any described loci for the species The number of alleles for polymorphic loci ranged from 2 to 16. Only one locus (Dft12) presented deviations of Hardy-Weinberg equilibrium, possibly due to the presence of null alleles. No pair of loci was in linkage disequilibrium. The genetic diversity varied from 0.08 to 0.91 and the observed heterozygosity from 0.07 to 0.80. The inbreeding coefficient for the population did not differ significantly from zero. The software Bottleneck indicated a possible occurrence of population bottleneck. The sex ratio was the expected 1:1. The described microsatellites amplified with success in other two species of the family Dendrocolaptidae (Xyphorhynchus fuscus and Sittasomus griseicapillus), indicating its potential use for population analysis of related taxa. The study produced valuable genetic tools for studies that seek to understand the diversity and genetic structure of the species D. turdina and possibly related groups. The analysis of the molecular biodiversity of species in habitats critically endangered, as the Atlantic forest, may be useful for conservation plans and management, aiding in the recognition and characterization of areas with larger genetic resources, in order to preserve the largest possible variability.